Hubungan Adiksi Game Online dengan Prokrastinasi Akademik - Adejuna, Febby Wulandari; Ardi, Zadrian (MASALIQ, 2024)
This study is motivated by the growing problem among students today, namely academic procrastination and one of the factors that influence academic procrastination is the behavior of addiction or online game addiction. This study aims to describe online game addiction and student academic procrastination, and to determine the relationship between online game addiction and student academic procrastination. The research method used in this study is quantitative with a descriptive correlational approach. The sample of this study was 121 students selected using purposive sampling technique. The instruments used in this study are online game addiction instruments and academic procrastination instruments. The data were processed with statistical techniques to determine the percentage value processed in the Microsoft excel program, to find the relationship between the two variables used the Pearson product moment technique. The results of this study show: 1) Online Game Addiction in MTsN 3 Padang students is generally in the moderate category with an average achievement score of 121.41 (55.37%), 2) Academic Procrastination in MTsN 3 Padang students in general is in the moderate category with an average score of 82.05 (76.86%), 3) There is a significant positive relationship between Online Game Addiction and Academic Procrastination of MTsN 3 Padang students with a correlation coefficient of 0.587 and a significance level of 0.000. This means that the higher the student's Online Game Addiction, the higher the Academic Procrastination in students, and vice versa, the lower the student's Online Game Addiction, the lower the Academic Procrastination in students.